Description of the fourth species of Trichoderes Chevrolat (Coleoptera, Cerambycidae, Prioninae) - Heffern, Daniel; Santos-Silva, Antonio; Berghe, Eric Van Den (Zootaxa, 2025)
A new species of Trichoderes Chevrolat, 1843 from Honduras is described and illustrated. An updated key to species of the genus is presented, along with photographs of all species currently included in the genus.